Parents’ use of coercive and indulgent feeding practices for children with avid eating behaviour: an Ecological Momentary Assessment study - Abigail Pickard; Katie L. Edwards; Claire Farrow; Emma Haycraft; Moritz Herle; Clare Llewellyn; Helen Croker; Alice Kininmonth; Jacqueline Blissett (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Children with avid eating behaviour display high food responsiveness, high emotional overeating and low sensitivity to fullness; behaviours which may increase the risk of obesity and are challenging for parents to manage. This study explores the situational predictors of coercive or indulgent feeding practices among parents of children with avid eating behaviours using Ecological Momentary Assessment (EMA). Methods The study involved 109 parents of 3-5-year-old children exhibiting avid eating behaviour. Over 10 days, participants completed EMA surveys via a mobile app to report on their mood, stress, feeding goals, and feeding practices during eating occasions. Multilevel modelling was used to assess how parental mood, goals, and the eating context (e.g., meal versus snack, public versus private setting) influenced feeding practices. Results Parents were more likely to use specific coercive or indulgent feeding practices when experiencing higher stress, when aiming to avoid mealtime conflict, and during meals versus snacks. A negative meal atmosphere and a public setting also increased the likelihood of certain indulgent practices. Notably, parents were more likely to report giving their child food to calm them down or help manage their behaviour when the meal atmosphere was perceived as negative and if they aimed to reduce conflict at the meal. The findings highlight that the context of feeding occasions significantly drives the use of coercive or indulgent feeding practices. Conclusions Parental stress, goals, and the eating context are key determinants of coercive or indulgent feeding practices with children exhibiting avid eating behaviours. Interventions to support parents should consider these dynamic factors, promoting healthier feeding strategies tailored to real-life contexts.